Template-free self-assembly of mesoporous ZnO nanocluster/ polymethyl methacrylate based anisotropic nanocomposite thin films with enhanced interfacial interactions and tuneable optical properties - Awasthi S.; Mohan A.; Singh K.K. (My University, 2025)
Nature inspired biomimetic growth of anisotropic, hierarchical nanostructures could offer insight into new and exciting crystalline properties for advanced multifunctional applications. Our study demonstrates diethanolamine-mediated mesoscopic self-assembly of semiconducting ZnO Quantum Dots (3-5 nm) into lattice-aligned, symmetrical superstructures (40-50 nm) via non-classical oriented attachment (OA) crystal growth observed in various biomineralization processes. Multifunctional nanocomposite thin films of self-assembled nanostructures and polymethyl methacrylate were spin-coated onto plasma-treated Si wafers and the surface and interfacial properties were rigorously studied. HR-TEM images depicted the OA growth process with neighboring nano-crystals having perfectly aligned lattices. Preferential orientation of the thin films along <100> direction was evident from the XRD data. Quantum confinement in ZnO QDs and surface defect originating sharp green PL emission were examined through UV-Vis absorption and Photoluminescence spectra respectively. DLS and Zeta potential studies of surface-engineered colloidal superstructures established excellent long-term physico-chemical stability with no agglomeration or transparency loss observed in ZnO mesocrystal suspension even after 6 months. Diethanolamine, due to its dual functionality radically enhanced the interaction between polar ZnO and non-polar PMMA matrix resulting in highly stable thin films (Class II hybrids) with enhanced surface and interfacial properties as evident from the extremely low surface roughness and homogenous nanofiller dispersion observed in AFM and FE-SEM studies. Chemical interactions at the interface were also established quantitatively by XPS binding energy measurements which suggested hydrogen bonds and covalent bonds between organic-inorganic phases promoted via diethanolamine surface engineering. © 2023 IOP Publishing Ltd.